Porous beryllium oxide ceramic and preparation method thereof
Through the combination and synergy of nano beryllium oxide and other materials of a specific proportion, combined with cold isostatic pressing molding and high-temperature sintering processes, the problems of low porosity, low strength and high sintering difficulties of porous beryllium oxide ceramics are solved, and the performance of the ceramic is achieved comprehensively improved.
Patent Information
- Application Number
- CN202411802579.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The existing porous beryllium oxide ceramics have low porosity, low strength and difficult sintering process, resulting in problems such as poor molding.
A specific ratio of nanoberyllium oxide, nanomagnesium oxide, nanoaluminum silicate, polyvinyl butyral, field cyanine powder and anhydrous ethanol are used to improve the porosity and strength of the ceramics through synergistic effects, and a cold isostatic pressing and high-temperature sintering are used.
The porosity and strength of porous beryllium oxide ceramics have been significantly improved, the molding and sintering problems have been solved, and the overall improvement of ceramic performance has been achieved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous ceramics, and in particular to a porous beryllium oxide ceramic and a preparation method thereof. Background Art
[0002] Beryllium oxide ceramics have always been an important component for electronic devices. Because of its high thermal conductivity, good insulation, thermal shock resistance, low loss and good chemical stability, it is widely used in the heat dissipation of high-power devices such as aviation, and has been widely used in electronic vacuum devices, high-power module thick film circuits, packaging devices, and optoelectronic devices.
[0003] Methods for preparing porous ceramic powders include gel method, emulsion method, emulsion precipitation method, etc. These methods all require the use of organic matter as pore formers. The porous powders need to be dried during the preparation process. The pore formers undergo thermal decomposition, combustion decomposition, sublimation, etc. during the powder drying process to achieve pore formation. The introduction and removal of pore formers will affect the sintering process; at the same time, the distribution of pore formers during the preparation process will also affect the porosity, pore size, strength, grain size and other properties of porous ceramics.
[0004] Most of the currently used beryllium oxide porous ceramics use a controlled amount of paraffin wax to form a certain porosity through low-temperature sintering to achieve the purpose of being porous. This type of porous ceramic has low strength due to the low sintering temperature, is not conducive to later processing, has low porosity, and has poor formability. Summary of the invention
[0005] In view of the above analysis, the present invention aims to provide a porous beryllium oxide ceramic and a preparation method thereof, so as to solve at least one of the problems of the porous beryllium oxide ceramic prepared by the existing method, namely, low porosity, low strength, difficult sintering process, easy powder aggregation and poor molding caused by sintering.
[0006] In a first aspect, the present invention provides a porous beryllium oxide ceramic, which is made of the following raw materials, in parts by weight: 65-85 parts of nano-beryllium oxide, 0.33-0.43 parts of nano-magnesium oxide, 0.33-0.43 parts of nano-aluminum silicate, 4-8 parts of polyvinyl butyral, 1-4 parts of sesbania powder and 12-30 parts of anhydrous ethanol.
[0007] Furthermore, the particle size of the nano-beryllium oxide is 100-200 nm, the particle size of the nano-magnesium oxide is 50-150 nm, and the particle size of the nano-aluminum silicate is 50-150 nm.
[0008] Furthermore, the particle size of the sesbania powder is 15-25 μm.
[0009] Furthermore, the porous beryllium oxide ceramic has a porosity of 22-28%, a room temperature flexural strength of ≥140 MPa, and a grain size of ≤20 μm.
[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned porous beryllium oxide ceramic, comprising the following steps:
[0011] (1) Weigh each raw material according to its weight and set aside;
[0012] (2) adding polyvinyl butyral into anhydrous ethanol to dissolve to obtain solution A;
[0013] (3) dissolving sesbania powder in water to obtain solution B, and mixing solution A and solution B to obtain a mixed solution;
[0014] (4) adding nano-beryllium oxide, nano-magnesium oxide and nano-aluminum silicate into the mixed solution, dispersing them uniformly, spray granulating them, and drying them to obtain powder;
[0015] (5) The powder is cold isostatically pressed and sintered at high temperature to obtain the porous beryllium oxide ceramic.
[0016] Furthermore, in step (2), the dissolution is carried out under ultrasound, the power of the ultrasound is 1000-1200W, and the ultrasound time is 30-40min.
[0017] Furthermore, in step (3), the mass fraction of the sesbania powder in solution B is 10-15%.
[0018] Furthermore, in step (4), the dispersion is carried out under ultrasonic conditions, the ultrasonic power is 1400-1800W, and the ultrasonic time is 2-4h.
[0019] Furthermore, in step (5), the cold isostatic pressing pressure is 120-150 MPa, and the holding time is 1-2 min.
[0020] Furthermore, in step (5), the high temperature sintering temperature is 1600-1700°C.
[0021] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0022] (1) The present invention combines nano-beryllium oxide, nano-magnesium oxide, nano-aluminum silicate, polyvinyl butyral, sesbania powder and anhydrous ethanol in a specific ratio, and the substances work synergistically to improve the porosity, strength and other properties of porous beryllium oxide ceramics. Among them, magnesium oxide, as a sintering aid, can reduce the sintering temperature, reduce energy consumption, and activate the lattice to improve the thermal shock resistance of the ceramic. Polyvinyl butyral has the functions of bonding, pore formation and molding, and anhydrous ethanol has the functions of molding and lubrication; sesbania powder improves the sintering properties of porous beryllium oxide ceramics, can promote diffusion and bonding between ceramic particles, accelerate the sintering process, reduce the sintering temperature, improve strength, increase porosity, and is easy to mold during cold isostatic pressing.
[0023] (2) The present invention has found through a large number of experiments that polyvinyl butyral and sesbania powder show good complementarity in the preparation of porous beryllium oxide. Polyvinyl butyral mainly provides bonding and molding properties, while sesbania powder mainly plays a role in thickening and pore structure regulation. During the preparation of porous beryllium oxide, the two interact with each other, thereby enhancing the binding force between beryllium oxide particles and stabilizing the pore structure. Through synergistic effects, polyvinyl butyral and sesbania powder can significantly improve the porosity and molding properties of porous beryllium oxide. The increase in porosity helps to increase the specific surface area and adsorption capacity of the material, while good molding properties make porous beryllium oxide more stable and reliable during preparation and application. Through the carefully designed combination of ingredients and synergistic mechanism, the synergistic effect of various substances enables porous beryllium oxide to achieve good sintering at high temperature, achieving a comprehensive improvement in the performance of porous beryllium oxide ceramics, and opening up a broader prospect for the research and development and application of ceramic materials.
[0024] (3) The method of the present invention first adds polyvinyl butyral to anhydrous ethanol to dissolve it, then dissolves the sesbania powder in water, and then mixes and adds nano-beryllium oxide, nano-magnesium oxide, and nano-aluminum silicate. The prepared powder has good formability and can be cold isostatically pressed. The porous beryllium oxide ceramic prepared by the cold isostatic pressing method of the present invention and the raw materials obtained have small grain size and high strength, which solves the problem of forming and sintering of porous beryllium oxide ceramics.
[0025] (4) The porous beryllium oxide ceramic of the present invention has a porosity of 26.5-28.0%, a room temperature flexural strength of 150-168 MPa, and a grain size of 8.1-11.8 μm.
[0026] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description. DETAILED DESCRIPTION
[0027] A specific embodiment of the present invention discloses a porous beryllium oxide ceramic, which is made of the following raw materials in parts by weight:
[0028] Nano-beryllium oxide: 65-85 parts, for example, 65 parts, 67 parts, 69 parts, 71 parts, 73 parts, 75 parts, 77 parts, 79 parts, 81 parts, 83 parts, 85 parts;
[0029] Nano magnesium oxide: 0.33-0.43 parts, for example, 0.33 parts, 0.34 parts, 0.35 parts, 0.36 parts, 0.37 parts, 0.38 parts, 0.39 parts, 0.40 parts, 0.41 parts, 0.42 parts, 0.43 parts;
[0030] Nano-aluminum silicate: 0.33-0.43 parts, for example, 0.33 parts, 0.34 parts, 0.35 parts, 0.36 parts, 0.37 parts, 0.38 parts, 0.39 parts, 0.40 parts, 0.41 parts, 0.42 parts, 0.43 parts;
[0031] Polyvinyl butyral: 4-8 parts, for example, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts;
[0032] Sesbania powder: 1-4 parts, for example, 1 part, 2 parts, 3 parts, 4 parts;
[0033] Anhydrous ethanol: 12-30 parts, for example, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts.
[0034] The present invention combines nano beryllium oxide, nano magnesium oxide, nano aluminum silicate, polyvinyl butyral, sesbania powder and anhydrous ethanol in a specific ratio, and the substances act synergistically to improve the porosity, strength and other properties of porous beryllium oxide ceramics. Among them, magnesium oxide, as a sintering aid, can reduce the sintering temperature and reduce energy consumption. Magnesium oxide can also activate the lattice and improve the thermal shock resistance of the ceramic. Polyvinyl butyral has the functions of bonding, pore formation and molding, and anhydrous ethanol has the functions of molding and lubrication; sesbania powder has the function of improving the sintering performance of porous beryllium oxide ceramics, can promote diffusion and bonding between ceramic particles, accelerate the sintering process, reduce the sintering temperature, improve the strength, increase the porosity, and is easy to mold during cold isostatic pressing.
[0035] The present invention has found through a large number of tests that polyvinyl butyral and sesbania powder show good complementarity when preparing porous beryllium oxide, polyvinyl butyral mainly provides bonding and molding performance, while sesbania powder mainly plays a role in thickening and pore structure regulation; during the preparation process of porous beryllium oxide, the two interact with each other, thereby enhancing the binding force between beryllium oxide particles and stabilizing the pore structure; through synergistic effect, polyvinyl butyral and sesbania powder can significantly improve the porosity and molding performance of porous beryllium oxide, the improvement of porosity helps to increase the specific surface area and adsorption capacity of the material, and the good molding performance makes the porous beryllium oxide more stable and reliable during the preparation and application process; through the carefully designed component combination and synergistic effect mechanism, the synergistic effect of various substances enables the porous beryllium oxide to achieve good sintering at high temperature, realizes the comprehensive improvement of the performance of porous beryllium oxide ceramics, and opens up a broader prospect for the research and development and application of ceramic materials.
[0036] In a specific embodiment, the particle size of the nano-beryllium oxide is 100-200nm, for example, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, the particle size of the nano-magnesium oxide is 50-150nm, for example, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, and the particle size of the nano-aluminum silicate is 50-150nm, for example, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm.
[0037] It should be noted that the inventors have found through a large number of experiments that the porous beryllium oxide ceramic material prepared with the above-mentioned particle size has higher strength.
[0038] In a specific embodiment, the particle size of the sesbania powder is 15-25 μm, for example, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm.
[0039] The use of the above-mentioned particle size of sesbania powder can significantly improve the strength and porosity of the ceramic material. If the particle size is too high or too low, the strength and porosity will be reduced.
[0040] In a specific embodiment, the porosity of the porous beryllium oxide ceramic is 22-28%, for example, 22%, 23%, 24%, 25%, 26%, 27%, 28%, the room temperature flexural strength is ≥140MPa, for example, 140-160MPa, and the grain size is ≤20μm, for example, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm.
[0041] Another specific embodiment of the present invention discloses a method for preparing the porous beryllium oxide ceramic, comprising the following steps:
[0042] (1) Weigh each raw material according to its weight and set aside;
[0043] (2) adding polyvinyl butyral into anhydrous ethanol to dissolve to obtain solution A;
[0044] (3) dissolving sesbania powder in water to obtain solution B, and mixing solution A and solution B to obtain a mixed solution;
[0045] (4) adding nano-beryllium oxide, nano-magnesium oxide and nano-aluminum silicate into the mixed solution, dispersing them uniformly, spray granulating them, and drying them to obtain powder;
[0046] (5) The powder is cold isostatically pressed and sintered at high temperature to obtain the porous beryllium oxide ceramic.
[0047] It should be noted that the method of the present invention first adds polyvinyl butyral to anhydrous ethanol for dissolution, and after dissolving sesbania powder in water, mixes and adds nano beryllium oxide, nano magnesium oxide, and nano aluminum silicate, and the prepared powder has good formability and can be cold isostatically pressed. The porous beryllium oxide ceramic prepared by the cold isostatic pressing method and raw materials of the present invention has a small grain size and high strength, which solves the problem of forming and sintering of porous beryllium oxide ceramics.
[0048] In a specific embodiment, in step (2), the dissolution is carried out under ultrasound, the power of the ultrasound is 1000-1200 W, for example, 1000 W, 1020 W, 1040 W, 1060 W, 1080 W, 1100 W, 1120 W, 1140 W, 1160 W, 1180 W, 1200, and the ultrasound time is 30-40 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min, 40 min.
[0049] In a specific embodiment, in step (3), the mass fraction of the sesbania powder in solution B is 10-15%, for example, 10%, 11%, 12%, 13%, 14%, 15%.
[0050] It should be noted that when the mass fraction of sesbania powder is as mentioned above, the obtained powder has good formability.
[0051] In a specific embodiment, in step (4), the dispersion is carried out under ultrasonic conditions, the power of the ultrasound is 1400-1800 W, for example, 1400 W, 1450 W, 1500 W, 1550 W, 1600 W, 1650 W, 1700 W, 1750 W, 1800 W, and the ultrasound time is 2-4 h, for example, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3.0 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h, 4.0 h.
[0052] In a specific embodiment, in step (5), the cold isostatic pressing pressure is 120-150 MPa, for example, 120 MPa, 125 MPa, 130 MPa, 135 MPa, 140 MPa, 145 MPa, 150 MPa, and the holding time is 1-2 min, for example, 1.1 min, 1.2 min, 1.3 min, 1.4 min, 1.5 min, 1.6 min, 1.7 min, 1.8 min, 1.9 min, 2 min.
[0053] It should be noted that the temperature of cold isostatic pressing is room temperature. Through a large number of experiments, it is found that the porous ceramics prepared by the above pressure and time have higher strength and smaller grain size.
[0054] In a specific embodiment, in step (5), the high temperature sintering temperature is 1600-1700°C, for example, 1600°C, 1610°C, 1620°C, 1630°C, 1640°C, 1650°C, 1660°C, 1670°C, 1680°C, 1690°C, 1700°C.
[0055] The technical solution of the present invention is further explained below in conjunction with specific embodiments.
[0056] Example 1
[0057] The porous beryllium oxide ceramic of this embodiment is made of the following raw materials in parts by weight: 65 parts of nano-beryllium oxide, 0.33 parts of nano-magnesium oxide, 0.33 parts of nano-aluminum silicate, 4 parts of polyvinyl butyral, 4 parts of sesbania powder and 12 parts of anhydrous ethanol. The particle size of the nano-beryllium oxide is 100 nm, the particle size of the nano-magnesium oxide is 50 nm, the particle size of the nano-aluminum silicate is 50 nm, and the particle size of the sesbania powder is 15 μm.
[0058] A method for preparing a porous beryllium oxide ceramic in this embodiment includes the following steps:
[0059] (1) Weigh each raw material according to its weight and set aside;
[0060] (2) adding anhydrous ethanol to polyvinyl butyral and dissolving it under ultrasound, the ultrasonic power is 1000 W, and the ultrasonic time is 40 min, to obtain solution A;
[0061] (3) dissolving sesbania powder in water to obtain solution B, wherein the mass fraction of the sesbania powder in solution B is 10%, and mixing solution A and solution B to obtain a mixed solution;
[0062] (4) adding nano-beryllium oxide, nano-magnesium oxide and nano-aluminum silicate to the mixed solution, dispersing them evenly under ultrasound, the power of the ultrasound is 1400 W, the ultrasound time is 4 h, spray granulation, and drying to obtain powder;
[0063] (5) The powder is cold isostatically pressed and sintered at high temperature, wherein the cold isostatic pressing pressure is 120 MPa, the holding time is 2 min, and the high-temperature sintering temperature is 1600° C. to obtain the porous beryllium oxide ceramic.
[0064] Example 2
[0065] The porous beryllium oxide ceramic of this embodiment is made of the following raw materials, in parts by weight: 75 parts of nano-beryllium oxide, 0.38 parts of nano-magnesium oxide, 0.38 parts of nano-aluminum silicate, 6 parts of polyvinyl butyral, 2.5 parts of sesbania powder and 21 parts of anhydrous ethanol. The particle size of the nano-beryllium oxide is 150 nm, the particle size of the nano-magnesium oxide is 100 nm, the particle size of the nano-aluminum silicate is 100 nm, and the particle size of the sesbania powder is 20 μm.
[0066] A method for preparing a porous beryllium oxide ceramic in this embodiment includes the following steps:
[0067] (1) Weigh each raw material according to its weight and set aside;
[0068] (2) adding anhydrous ethanol to polyvinyl butyral and dissolving it under ultrasound, the ultrasonic power is 1100 W, and the ultrasonic time is 35 min, to obtain solution A;
[0069] (3) dissolving sesbania powder in water to obtain solution B, wherein the mass fraction of sesbania powder in solution B is 12.5%, and mixing solution A and solution B to obtain a mixed solution;
[0070] (4) adding nano-beryllium oxide, nano-magnesium oxide and nano-aluminum silicate to the mixed solution, dispersing them evenly under ultrasound, the power of the ultrasound is 1600 W, the ultrasound time is 3 h, spray granulation, and drying to obtain powder;
[0071] (5) The powder is cold isostatically pressed and sintered at high temperature, wherein the cold isostatic pressing pressure is 135 MPa, the holding time is 1.5 min, and the high-temperature sintering temperature is 1650° C. to obtain the porous beryllium oxide ceramic.
[0072] Example 3
[0073] The porous beryllium oxide ceramic of this embodiment is made of the following raw materials, in parts by weight: 85 parts of nano-beryllium oxide, 0.43 parts of nano-magnesium oxide, 0.43 parts of nano-aluminum silicate, 8 parts of polyvinyl butyral, 1 part of sesbania powder, and 30 parts of anhydrous ethanol. The particle size of the nano-beryllium oxide is 200 nm, the particle size of the nano-magnesium oxide is 150 nm, the particle size of the nano-aluminum silicate is 150 nm, and the particle size of the sesbania powder is 25 μm.
[0074] A method for preparing a porous beryllium oxide ceramic in this embodiment includes the following steps:
[0075] (1) Weigh each raw material according to its weight and set aside;
[0076] (2) adding anhydrous ethanol to polyvinyl butyral and dissolving it under ultrasound, the ultrasonic power is 1200 W, and the ultrasonic time is 30 min, to obtain solution A;
[0077] (3) dissolving sesbania powder in water to obtain solution B, wherein the mass fraction of the sesbania powder in solution B is 15%, and mixing solution A and solution B to obtain a mixed solution;
[0078] (4) adding nano-beryllium oxide, nano-magnesium oxide and nano-aluminum silicate to the mixed solution, dispersing them evenly under ultrasound, the power of the ultrasound is 1800 W, the ultrasound time is 2 h, spray granulation is performed, and drying is performed to obtain a powder;
[0079] (5) The powder is cold isostatically pressed and sintered at high temperature, wherein the cold isostatic pressing pressure is 150 MPa, the holding time is 1 min, and the high-temperature sintering temperature is 1700° C. to obtain the porous beryllium oxide ceramic.
[0080] Example 4
[0081] The porous beryllium oxide ceramic of this embodiment is made of the following raw materials, in parts by weight: 70 parts of nano-beryllium oxide, 0.40 parts of nano-magnesium oxide, 0.40 parts of nano-aluminum silicate, 5 parts of polyvinyl butyral, 2 parts of sesbania powder and 20 parts of anhydrous ethanol. The particle size of the nano-beryllium oxide is 180 nm, the particle size of the nano-magnesium oxide is 120 nm, the particle size of the nano-aluminum silicate is 120 nm, and the particle size of the sesbania powder is 22 μm.
[0082] A method for preparing a porous beryllium oxide ceramic in this embodiment includes the following steps:
[0083] (1) Weigh each raw material according to its weight and set aside;
[0084] (2) adding anhydrous ethanol to polyvinyl butyral and dissolving it under ultrasound, the ultrasound power is 1050 W, and the ultrasound time is 38 min, to obtain solution A;
[0085] (3) dissolving sesbania powder in water to obtain solution B, wherein the mass fraction of sesbania powder in solution B is 14%, and mixing solution A and solution B to obtain a mixed solution;
[0086] (4) adding nano-beryllium oxide, nano-magnesium oxide and nano-aluminum silicate to the mixed solution, dispersing them evenly under ultrasound, the power of the ultrasound is 1500 W, the ultrasound time is 3 h, spray granulation, and drying to obtain powder;
[0087] (5) The powder is cold isostatically pressed and sintered at high temperature, wherein the cold isostatic pressing pressure is 145 MPa, the holding time is 1.8 min, and the high-temperature sintering temperature is 1680° C. to obtain the porous beryllium oxide ceramic.
[0088] Comparative Example 1
[0089] The raw materials and preparation method of a porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that the particle size of nano-beryllium oxide is 300 nm, the particle size of nano-magnesium oxide is 180 nm, and the particle size of nano-aluminum silicate is 180 nm.
[0090] Comparative Example 1-1
[0091] The raw materials and preparation method of a porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that the particle size of nano-beryllium oxide is 80 nm, the particle size of nano-magnesium oxide is 40 nm, and the particle size of nano-aluminum silicate is 40 nm.
[0092] Comparative Example 2
[0093] The raw materials and preparation method of the porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that the particle size of the sesbania powder is 10 μm.
[0094] Comparative Example 2-1
[0095] The raw materials and preparation method of the porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that the particle size of the sesbania powder is 30 μm.
[0096] Comparative Example 3
[0097] The raw materials and preparation method of the porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that in step (3), the mass fraction of sesbania powder is 8%.
[0098] The test found that the powder could not be formed after cold isostatic pressing.
[0099] Comparative Example 3-1
[0100] The raw materials and preparation method of the porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that in step (3), the mass fraction of sesbania powder is 18%.
[0101] The test found that the powder could not be formed after cold isostatic pressing.
[0102] Comparative Example 4
[0103] The raw materials and preparation method of the porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that in step (3), the cold isostatic pressing pressure is 110 MPa and the holding time is 3 min.
[0104] Comparative Example 4-1
[0105] The raw materials and preparation method of the porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that in step (3), the cold isostatic pressing pressure is 160 MPa and the holding time is 0.5 min.
[0106] Comparative Example 5
[0107] The raw materials and preparation method of a porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that steps (2) and (3) are removed from the preparation method, and in step (4), the raw materials are directly mixed and evenly dispersed, and dried to obtain a powder.
[0108] The test found that the powder could not be formed after cold isostatic pressing.
[0109] Comparative Example 6
[0110] The raw materials and preparation method of a porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that nano-magnesium oxide is replaced by nano-silicon dioxide in the raw materials, and the total mass is kept unchanged by changing the amount of nano-beryllium oxide added.
[0111] Comparative Example 7
[0112] The raw materials and preparation method of a porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that the sesbania powder is removed from the raw materials, and the total mass is kept unchanged by changing the amount of nano-beryllium oxide added.
[0113] Comparative Example 8
[0114] The raw materials and preparation method of a porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that the amount of nano-beryllium oxide is 60 parts and the amount of polyvinyl butyral is 16 parts.
[0115] Comparative Example 9
[0116] The raw materials and preparation method of a porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that the nano-aluminum silicate is removed from the raw materials, and the total mass is kept unchanged by changing the amount of nano-beryllium oxide added.
[0117] Comparative Example 10
[0118] The raw materials and preparation method of a porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that polyvinyl butyral is removed from the raw materials, and the total mass is kept unchanged by changing the amount of nano-beryllium oxide added.
[0119] Comparative Example 11
[0120] The raw materials and preparation method of the porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that in step (5) of the preparation method, the sintering temperature is 1550°C.
[0121] Comparative Example 12
[0122] The raw materials and preparation method of the porous beryllium oxide ceramic in this comparative example are the same as those in Example 2, except that in step (5) of the preparation method, the sintering temperature is 1750°C.
[0123] Test Example 1
[0124] The properties of the porous beryllium oxide ceramics prepared in Examples 1-4 and Comparative Examples 1-9 were tested respectively. The results are shown in Table 1.
[0125] Table 1
[0126] Group Porosity (%) Room temperature flexural strength (MPa) Grain size (μm) Example 1 26.8 150 11.8 Example 2 28.0 168 8.1 Example 3 27.1 162 9.2 Example 4 26.5 159 8.6 Comparative Example 1 22.3 141 12.3 Comparative Example 1-1 21.5 143 12.9 Comparative Example 2 20.4 142 13.2 Comparative Example 2-1 21.6 139 14.5 Comparative Example 3 -- -- -- Comparative Example 3-1 -- -- -- Comparative Example 4 20.1 138 20.9 Comparative Example 4-1 19.8 136 21.6 Comparative Example 5 -- -- -- Comparative Example 6 18.3 137 21.4 Comparative Example 7 17.9 136 24.1 Comparative Example 8 19.4 143 22.6 Comparative Example 9 18.1 134 23.5 Comparative Example 10 17.1 129 26.8 Comparative Example 11 19.8 139 23.6 Comparative Example 12 21.3 128 25.6
[0127] Compared with Example 2, the particle sizes of nano-beryllium oxide and nano-magnesium oxide in Comparative Examples 1 and 1-1 are not within the range defined by the present invention, and the obtained porous beryllium oxide ceramics have lower porosity and room temperature flexural strength and larger grain size.
[0128] Compared with Example 2, the particle size of the sesbania powder in Comparative Examples 2 and 2-1 is not within the range defined by the present invention, and the obtained porous beryllium oxide ceramics have lower porosity and room temperature flexural strength and larger grain size.
[0129] Compared with Example 2, the mass fraction of the sesbania powder in Comparative Examples 3 and 3-1 is not within the range defined in the present invention, and the powder cannot be formed after cold isostatic pressing.
[0130] Compared with Example 2, the cold isostatic pressing pressure and holding time of Comparative Examples 4 and 4-1 are not within the range defined by the present invention, and the obtained porous beryllium oxide ceramics have lower porosity and room temperature flexural strength and larger grain size.
[0131] Compared with Example 2, in Comparative Example 5, the raw materials are directly mixed without using the method of the present invention, and the powder cannot be formed after cold isostatic pressing.
[0132] Compared with Example 2, in Comparative Examples 6-7 and 9-10, nano-magnesium oxide is replaced with nano-silicon dioxide, or sesbania powder, nano-aluminum silicate or polyvinyl butyral is removed from the raw materials, and the obtained porous beryllium oxide ceramics have lower porosity and room temperature flexural strength, and larger grain size. This shows that the raw materials of the present invention are used, and the porous beryllium oxide ceramics with high porosity, high strength and small grains of the present application can be obtained through the synergistic effect of various raw materials.
[0133] Comparative Example 8 Compared with Example 2, the porous beryllium oxide ceramic obtained by using the raw materials of the present invention in a ratio not specified in the present application has lower porosity and room temperature flexural strength and larger grain size.
[0134] Compared with Example 2, the porous beryllium oxide ceramics prepared in Comparative Examples 11-12 at a sintering temperature other than the present invention have lower porosity and room temperature flexural strength, and larger grain size.
[0135] The inventors have also conducted the above tests on other embodiments, and the results are basically the same. Due to limited space, they are not listed one by one.
[0136] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A porous beryllium oxide ceramic, characterized in that: The invention comprises the following raw materials in parts by weight: 65-85 parts of nano-beryllium oxide, 0.33-0.43 parts of nano-magnesium oxide, 0.33-0.43 parts of nano-aluminum silicate, 4-8 parts of polyvinyl butyral, 1-4 parts of sesbania powder and 12-30 parts of anhydrous ethanol.
2. The porous beryllium oxide ceramic according to claim 1, characterized in that: The particle size of the nanometer beryllium oxide is 100-200nm, the particle size of the nanometer magnesium oxide is 50-150nm, and the particle size of the nanometer aluminum silicate is 50-150nm.
3. A porous beryllium oxide ceramic according to claim 1 or 2, characterized in that: The particle size of the sesbania powder is 15-25 μm.
4. A porous beryllium oxide ceramic according to claim 1 or 2, characterized in that: The porous beryllium oxide ceramic has a porosity of 22-28%, a room temperature flexural strength of ≥140MPa, and a grain size of ≤20μm.
5. A method for preparing the porous beryllium oxide ceramic according to any one of claims 1 to 4, characterized in that: The steps include: (1) Weigh each raw material according to its weight and set aside; (2) adding polyvinyl butyral into anhydrous ethanol to dissolve to obtain solution A; (3) dissolving sesbania powder in water to obtain solution B, and mixing solution A and solution B to obtain a mixed solution; (4) adding nano-beryllium oxide, nano-magnesium oxide and nano-aluminum silicate into the mixed solution, dispersing them uniformly, spray granulating them, and drying them to obtain powder; (5) The powder is cold isostatically pressed and sintered at high temperature to obtain the porous beryllium oxide ceramic.
6. The preparation method according to claim 5, characterized in that: In step (2), the dissolution is carried out under ultrasound, the power of the ultrasound is 1000-1200W, and the ultrasound time is 30-40min.
7. The preparation method according to claim 5, characterized in that: In step (3), the mass fraction of the sesbania powder in solution B is 10-15%.
8. The preparation method according to claim 5, characterized in that: In step (4), the dispersion is carried out under ultrasonic conditions, the ultrasonic power is 1400-1800W, and the ultrasonic time is 2-4h.
9. The preparation method according to claim 5, characterized in that: In step (5), the cold isostatic pressing pressure is 120-150 MPa, and the holding time is 1-2 min.
10. The preparation method according to claim 5, characterized in that: In step (5), the high temperature sintering temperature is 1600-1700°C.
Citation Information
Patent Citations
Mesoporous beta zeolite and preparation method thereof
CN107032369A
Thinning production method of beryllium oxide ceramic substrate
CN117069481A
The manufacture of refractory products
GB595588A
Improvements in or relating to the production of sintered beryllium oxide
GB936004A
Cited By
Preparation method of porous beryllium oxide ceramic chip
CN120647420A
A method for producing a porous beryllium oxide ceramic sheet
CN120647420B